Case Report: An Application of Wellbeing Science for the Development of Adolescent High-Performance Athletes in the Australian Football League - Hoare, Erin; Couston, Nicky; Hall, Kate (Frontiers in Psychology, 2022)
Elite athletes experience both universal and sport-related mental health risks. Young high-performance athletes on pathways to professional sport also face the additional challenges associated with the developmental period of adolescence and early adulthood, making prevention and mental health promotion critical in this population group. This community case study considers the wider youth mental well-being evidence base, alongside primary prevention in elite sport, and proposes a model of well-being for the specific implementation in youth high performance athletes in the Australian setting. The Mental Fitness Model is based on the PERMA theory of well-being, which comprises positive emotion, engagement, relationships, meaning, and accomplishment, and is tailored specifically to the unique needs of young high-performance athletes in Australia. The Model sits within a host of evidence-based, appropriately resourced, well-being science activities, coordinated by an overall strategy that allows monitoring and continuous improvement. As such, we propose this application of well-being science is highly novel for the youth high performance setting. Future work is needed to test the feasibility of this model in an applied context. Further work is also needed to integrate specifically cultural considerations for well-being, and to integrate the lived experiences of young people through participatory research. This model is proposed to hold unique promise to meet the mental well-being needs of young high-performance athletes, whilst promoting positive mental health that can track into adulthood.